Formulation of solution to prevent lysis time erythrocyte and detecting blood type - Amelia, Ria; Sari, Elfira Maya (Universitas Muhammadiyah Purwokerto, 2024)
Background: In the examination of blood type using the tube method, a test cell containing 5% erythrocytes of the solution volume is required. The blood type test using the tube method is carried out in hospital blood banks and in the educational world during practical activities. The obstacle in making a 5% erythrocyte solution is that erythrocytes are lysed so that it is made every day. In addition, making a 5% erythrocyte solution takes a long time so it is not efficient. Purpose: This study aims to find a solution that can maintain erythrocytes for a long time and detecting blood type.Method: This experimental study involved the preparation of 120 tubes containing 5% erythrocyte suspensions from blood types A, B, AB, and O. The samples were diluted in 10 different test solutions, including CPD, ACD, EDTA 5%, Heparin 3%, NaCl 0.9% + glucose (0.025%, 0.05%, 0.1%, 0.2%, and 0.3%), and NaCl 0.9% Daily lysis observations were performed using vortex mixing, centrifugation, and color assessment. The solution with the most extended stability was further tested for ABO blood grouping using the tube method to analyze agglutination patterns.Results: The test solution that can maintain erythrocytes for a long time is the citrate phosphate dextrose (CPD) solution. This solution can prevent erythrocytes for a long time and does not damage erythrocyte antigens. It can also detect blood types well, making blood type examination time more efficient.Conclusion: CPD solution successfully prevents erythrocyte lysis for a longer time compared to other solutions and functions in detecting blood type antibodies.